New Potential of Roxatidine Acetate Hydrochloride on Atopic Dermatitis Mouse Model, Human Keratinocytes, and Human Skin Equivalent Model - Kang, Yun-Mi; Lee, Minho; An, Hyo-Jin (Frontiers in Pharmacology, 2021)
Atopic dermatitis (AD) is a complex inflammatory skin disorder, characterized by a complicated pathophysiology and a wide range of clinical phenotypes. Roxatidine acetate chloride (RXA) is a precursor of Roxatidine and a histamine H2 receptor antagonist, used for the treatment of gastric ulcers. In this study, we aimed to examine whether RXA had anti-AD effects and determine the underlying molecular mechanism of RXA. The anti-AD effects were examined in Dermatophagoides farinae body (Dfb)-induced AD mouse model, tumor necrosis factor (TNF)-α/interferon (IFN)-γ-stimulated HaCaT keratinocytes, and human skin equivalent model using ELISA, histological analysis, immunohistochemistry, Western blot, and immunofluorescence. Results showed that RXA treatment significantly alleviated Dfb-induced AD skin symptoms and clinical severity in mice by decreasing the levels of immunoglobulin E, histamine, and inflammatory cytokines. RXA effectively inhibited the expression of adhesive molecules and recovered the filaggrin expression in Dfb-induced AD skin lesions and TNF-α/IFN-γ-stimulated HaCaT keratinocytes. Additionally, RXA significantly upregulated the expression of aryl hydrocarbon receptor and sirtuin1. The anti-AD effects of RXA were associated with suppressed nuclear factor kappa cascade. Overall, our results suggest that RXA may be a potential anti-AD candidate owing to its inhibitory effect against skin inflammation and protection of the skin barrier function in AD.